Framing public governance in Malaysia: rhetorical appeals through accrual accounting - Ferry,, Laurence; Zakaria, Zamzulaila; Zakaria, Zarina A.; Slack, Richard E. (Elsevier, 2018)
In government, the challenges of governance and anti-corruption are exacerbated by accounting not being fit for purpose. In developing countries, many governments adopt accrual accounting as a panacea. Drawing on Goffman's frame analysis, and rhetorical appeals to logic, credibility and emotion, this paper examines the adoption of accrual accounting in Malaysia. It was found accrual accounting has potential for keying governance and anti-corruption. However, rhetorical appeals that attempt to legitimate neo-liberalism and engender public support in the name of progress were hindered by perceptions of endemic corruption and relatively weak democratic institutions of 'good' governance common to developing countries.